PSYCHOLOGICAL DISTRESS WARGA BINAAN PEMASYARAKATAN (WBP) LAPAS KELAS IIA PALU - Milka (Jurnal Cakrawala Ilmiah, 2023)
Undergoing a criminal term raises various kinds of problems both physically and psychologically for Prison Assisted Residents (WBP) Class IIA Palu Prison. This is one of the factors WBP experienced stress during his detention period in prison. This study aims to find out the description Psychological Distress to Correctional Families (WBP) in Class IIA Palu Prison. This research uses a quantitative descriptive approach. The participants in this study consisted of 100 participants who were WBP Class IIA Palu prisons using techniques Accidental Sampling. Data collection was carried out using the DASS-42 scale developed by Lovibond and Lovibond (1995) which was adapted into Indonesian by Damanik, (2006) with a reliability value of 0.918. The results showed that 17% had low Psychological Distress levels, 59% moderate, 24% high. The scores obtained by the participants moved from a minimum score of 30 to a maximum score of 92 with a standard deviation of 14.27. From the results of the study, it can be concluded that most of the participants had a moderate level of Psychological Distress.